Libertad, unidad y movimiento: los límites de la teoría del caos aplicada a las ciencias sociales - Atienza, David (2017)
The impact of the postmodernism in the Social Sciences and the fall of the 19th century Marxism generated a epistemological void that was re-constructed by some intellectual currents using physic and mathematic theories as the Chaos Theory or dynamic non-lineal theories. This option, wide spread today among intellectuals, is trying to rescue the possibility to think in an epistemological center but at the same time it challenge human freedom suggesting a new deterministic model. In this paper we introduce the genesis of these ideas and propose a possible metaphysical and Christian recovery of Freedom, Unity, and Movement.